Flame-retardant compound and preparation method thereof
Through the synergy between modified nano core-shell flame retardant and magnesium hydroxide, glass fiber and montmorillonite powder, the problem of insufficient flame retardant performance of polyethylene cable outer sheath material is solved, and efficient heat absorption and Smoke suppression significantly improves the flame retardant and mechanical properties of the material.
Patent Information
- Application Number
- CN202411324388.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The outer sheath material of polyethylene cable has poor flame retardant properties, is prone to combustion and generates a lot of heat and smoke, threatening the safe use of the cable.
The synergistic effect of modified nano core-shell flame retardant with magnesium hydroxide, glass fiber and montmorillonite powder is adopted to make the flame retardant more evenly distributed in the polymer through nanotechnology to form a stable core-shell structure and carbon layer. Absorb heat and inhibit the generation of combustible gases, preventing the spread of combustion.
The flame retardant performance of the outer sheath material of polyethylene cable is significantly improved, heat and smoke generation is reduced, thermal stability and mechanical properties of the material are enhanced, and safety and reliability are improved.
Smart Images

Figure CN119192676A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flame-retardant composite materials, in particular to a doping component used for an outer sheath material of a polyethylene cable. Background Art
[0002] Polyethylene is a commonly used cable sheath material with excellent electrical insulation, physical and mechanical properties, and weather resistance. However, polyethylene has poor flame retardancy, is easy to burn and produces a lot of heat and smoke, which seriously threatens the safe use of cables. Therefore, improving the flame retardant properties of polyethylene is one of the important research directions of cable sheath materials. In recent years, researchers have developed a variety of flame retardant composite materials to improve the flame retardant properties of polyethylene. These composite materials are usually composed of polyethylene and various flame retardants, such as magnesium hydroxide, aluminum hydroxide, calcium carbonate, etc. These flame retardants can improve the flame retardant properties of polyethylene through different mechanisms, such as reducing heat, inhibiting smoke generation, and slowing down the burning rate.
[0003] A commonly used flame retardant composite material is magnesium hydroxide / polyethylene composite material. This composite material can significantly improve the flame retardant properties of polyethylene by adding magnesium hydroxide to polyethylene. Magnesium hydroxide can decompose at high temperatures to produce water and metal oxides, thereby reducing heat and smoke generation. At the same time, magnesium hydroxide can also improve the mechanical strength and weather resistance of polyethylene.
[0004] Another commonly used flame retardant composite material is calcium carbonate / polyethylene composite material. This composite material can improve the flame retardant properties and mechanical strength of polyethylene by adding calcium carbonate to polyethylene. Calcium carbonate can decompose at high temperatures to produce carbon dioxide, thereby reducing heat and smoke generation.
[0005] In addition to these commonly used flame retardant composite materials, many other types of flame retardant composite materials have been developed, such as composite materials containing phosphates, silicates, aluminates, etc. These composite materials can improve the flame retardant properties of polyethylene through different mechanisms, such as inhibiting the combustion reaction, reducing heat, and delaying the burning speed.
[0006] In summary, flame retardant composite materials are an effective method to improve the flame retardant properties of polyethylene cable sheath materials. By selecting appropriate flame retardants and preparation methods, polyethylene composite materials with excellent flame retardant properties can be obtained. These composite materials can be widely used in the field of cable sheath materials to improve the safe use performance of cables.
[0007] The modification methods of polyethylene mainly include the following:
[0008] 1. Cross-linking modification: The polyethylene molecular chains are cross-linked through a cross-linking agent to improve its mechanical strength and weather resistance.
[0009] 2. Blending modification: By blending different types of polymers, the mechanical strength and weather resistance of polyethylene can be improved.
[0010] 3. Filling modification: By adding various fillers to polyethylene, its mechanical strength and weather resistance are improved.
[0011] 4. Surface modification: By modifying the surface of polyethylene, its mechanical strength and weather resistance can be improved.
[0012] These modification methods can be used alone or in combination to improve the properties of polyethylene.
[0013] The application fields of polyethylene are very wide, including cable sheath materials, packaging materials, building materials, etc. In the field of cable sheath materials, polyethylene is widely used in power cables, communication cables and other fields due to its excellent electrical insulation properties, physical and mechanical properties and weather resistance.
[0014] However, polyethylene has poor flame retardancy, is easy to burn and produces a lot of heat and smoke, which seriously threatens the safe use of cables. Therefore, improving the flame retardancy of polyethylene is one of the important research directions of cable sheath materials.
[0015] In recent years, researchers have developed a variety of flame-retardant composite materials to improve the flame retardant properties of polyethylene. These composite materials are usually composed of polyethylene and various flame retardants, such as magnesium hydroxide, aluminum hydroxide, calcium carbonate, etc. These flame retardants can improve the flame retardant properties of polyethylene through different mechanisms, such as reducing heat, inhibiting smoke generation, and delaying the burning rate.
[0016] In summary, polyethylene is a commonly used cable sheath material with excellent electrical insulation properties, physical and mechanical properties, and weather resistance. However, its flame retardant properties are poor, and it is necessary to improve its flame retardant properties by modifying or adding flame retardants. Flame retardant composite materials are an effective method to improve the flame retardant properties of polyethylene cable sheath materials. By selecting suitable flame retardants and preparation methods, polyethylene composite materials with excellent flame retardant properties can be obtained. These composite materials can be widely used in the field of cable sheath materials to improve the safe use performance of cables. Summary of the invention
[0017] In order to improve the flame retardant properties of the outer sheath material of the polyethylene type cable, the present invention provides a flame retardant composite and a preparation method thereof, high-efficiency flame retardant properties: the modified nano core-shell flame retardant and magnesium hydroxide in the composite can decompose and absorb a large amount of heat at high temperature, reduce the temperature of the polymer surface, thereby effectively inhibiting the generation of combustible gas and preventing the spread of combustion; synergistic flame retardant effect: the various components in the composite, such as the modified nano core-shell flame retardant, magnesium hydroxide and glass fiber, further improve the flame retardant effect through synergistic effect. In particular, the application of nanotechnology makes the flame retardant more evenly distributed in the polymer, enhancing the overall flame retardant properties.
[0018] In order to achieve the above object, the present invention adopts the following technical solutions:
[0019] The flame retardant composite material comprises the following components in percentage by weight:
[0020]
[0021] The balance is montmorillonite powder.
[0022] Preferably, the flame retardant composite, wherein the flame retardant composite has the following mass percentage composition:
[0023]
[0024]
[0025] The balance is montmorillonite powder.
[0026] Preferably, the flame retardant composite, wherein the flame retardant composite has the following mass percentage composition:
[0027]
[0028] The balance is montmorillonite powder.
[0029] Preferably, in the flame retardant composite, the glass fiber has a diameter of 5-10 um and a length of 2-5 mm.
[0030] Preferably, in the flame retardant composite, the surfactant is polyoxyethylene lauryl ether.
[0031] Preferably, in the flame retardant composite, the preparation steps of the modified nano core-shell flame retardant are as follows:
[0032] In parts by weight, 40-65 parts of carbon nanotubes are added to an organic solvent containing a phosphorus nitrogen polymer and ethylenediamine, and the temperature is controlled at 70°C-80°C in an oil bath while stirring. Then, under nitrogen protection, 3-5 parts of initiator dibenzoyl peroxide are added, and ultrasonic water bath heating is used for 6h-10h. After the reaction is completed, the product is washed with deionized water for 5 times and vacuum freeze-dried.
[0033] Material selection and ratio:
[0034] Carbon nanotubes: As nanofillers, carbon nanotubes have excellent mechanical properties and conductive properties. Their application in flame retardants can significantly improve the thermal stability and flame retardant properties of materials.
[0035] Phosphorus nitrogen polymer and ethylenediamine: Phosphorus nitrogen polymer is a common flame retardant with good carbonization and gas phase flame retardant effects. Ethylenediamine, as a cross-linking agent, can enhance the mechanical properties and thermal stability of the material.
[0036] Reaction conditions:
[0037] Temperature control: Stirring in an oil bath at 70℃-80℃ can ensure the uniformity and stability of the reaction and avoid local overheating or incomplete reaction.
[0038] Nitrogen protection: Carrying out the reaction under nitrogen protection can prevent the occurrence of oxidation reaction and ensure the purity of the reaction and the quality of the product.
[0039] Use of initiator: Dibenzoyl peroxide as an initiator can effectively initiate the polymerization reaction and form a stable core-shell structure.
[0040] Ultrasonic water bath heating:
[0041] Application of ultrasound: Ultrasound can promote the uniform dispersion of reactants, increase reaction rate and efficiency, and help form a uniform nano core-shell structure.
[0042] Long-term heating: 6 to 10 hours of ultrasonic water bath heating can ensure the full progress of the reaction and form a stable nano core-shell structure.
[0043] Post-processing:
[0044] Deionized water washing: Multiple washings can remove unreacted raw materials and by-products to ensure the purity of the product.
[0045] Vacuum freeze drying: Vacuum freeze drying can effectively remove moisture and avoid material decomposition or performance degradation caused by high temperature drying process.
[0046] Summarize
[0047] This production step can effectively prepare a modified nano core-shell flame retardant with excellent flame retardant properties through reasonable material selection and precise process control. The synergistic effect of carbon nanotubes and phosphorus nitrogen polymers, as well as process methods such as ultrasound and nitrogen protection, ensure the uniformity and stability of the material. This method not only improves the flame retardant properties of the material, but also maintains good mechanical properties and thermal stability, and has broad application prospects.
[0048] Preferably, in the flame retardant composite, the amount of the organic solvent is 200 parts to 340 parts;
[0049] The organic solvent is dimethyl sulfoxide;
[0050] The phosphorus-nitrogen polymer is used in an amount of 30 to 60 parts;
[0051] The phosphorus-nitrogen polymer is poly(ethylene-chlorotrifluoroethylene);
[0052] The usage of the ethylenediamine is 10 parts to 15 parts.
[0053] The method for preparing the flame retardant composite as described above comprises the following steps:
[0054] (1) mixing the modified nano core-shell flame retardant, magnesium hydroxide and a surfactant, and heating the mixture at 80° C. to 90° C. for 180 min to 240 min;
[0055] (2) The mixture obtained in step (1) is homogeneously mixed with glass fiber and montmorillonite powder, and then dried and packaged.
[0056] For the above process steps, a high-speed stirrer (such as IKAT25 digital high shear stirrer) is used for stirring and mixing, while a constant temperature water bath (such as HH-6 digital constant temperature water bath) can be used for heating the reaction step.
[0057] It should be noted that the above process steps are only used to prepare flame retardant composites, and resin materials need to be added for composite filling treatment in actual application.
[0058] Beneficial effects of the present invention:
[0059] By combining modified nano core-shell flame retardant, magnesium hydroxide, glass fiber, montmorillonite powder and other substances together, a synergistic effect can be produced, thereby improving the flame retardant properties of the outer sheath material of the polyethylene cable.
[0060] The possible chemical reactions between the modified nano core-shell flame retardant and magnesium hydroxide include:
[0061] Magnesium hydroxide decomposes at high temperatures to produce water and metal oxides, thereby reducing heat and smoke generation.
[0062] The phosphorus-nitrogen polymer in the modified nano core-shell flame retardant reacts with ethylenediamine to form a stable core-shell structure, thereby improving the thermal stability and flame retardant properties of the material.
[0063] Possible chemical reactions between glass fiber and montmorillonite powder include:
[0064] Glass fibers deform and break at high temperatures, absorbing heat and slowing the material's burn rate.
[0065] Montmorillonite powder decomposes at high temperatures, producing gas and reducing the burning rate of the material.
[0066] The possible chemical reactions between the modified nano core-shell flame retardant, magnesium hydroxide, glass fiber and montmorillonite powder include:
[0067] The synergistic effect between these substances can improve the flame retardant properties of the material, thereby reducing heat and smoke generation.
[0068] The reaction between these substances can improve the thermal stability and mechanical strength of the material, thereby improving the safety and reliability of the material.
[0069] In summary, the beneficial effect of the present invention is that it can improve the flame retardant performance of the outer sheath material of the polyethylene type cable, thereby improving the safety and reliability of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 This is a structural schematic diagram of the modified nano core-shell flame retardant.
[0071] Figure 2 This is a scanning electron microscope image of the modified nano core-shell flame retardant. DETAILED DESCRIPTION
[0072] The present invention is described in more detail below in an exemplary manner.
[0073] The reagent raw materials involved in the present invention are mainly purchased from companies such as Xilong Chemical Co., Ltd., or can be purchased through other companies. In addition, the carbon nanotubes involved are multi-walled carbon nanotubes produced by Shenzhen Guoheng Qihang Technology Co., Ltd., with a purity of >98wt%, an inner diameter of 5-10nm, an outer diameter of 20-30nm, a length of 0.5-2um, and a bulk density of 0.09g / cm 3 , with a specific surface area of 250m 2 / g.
[0074] It should be noted that, in the present invention, the weight parts involved are in kilograms in practical applications.
[0075] Implementation Method 1
[0076] The flame retardant composite has the following mass percentage composition:
[0077]
[0078] The balance is montmorillonite powder.
[0079] As for the raw materials, the diameter of the glass fiber is 5um and the length is 5mm.
[0080] The surfactant is polyoxyethylene lauryl ether.
[0081] The preparation steps of the modified nano core-shell flame retardant are as follows:
[0082] In parts by weight, 40 parts of carbon nanotubes are added to an organic solvent containing a phosphorus nitrogen polymer and ethylenediamine, and the mixture is stirred while being controlled at 80°C in an oil bath, and then 3 parts of an initiator dibenzoyl peroxide are added under nitrogen protection, and an ultrasonic water bath is used to heat the mixture for 10 hours. After the reaction is completed, the mixture is washed with deionized water for 5 times, and then freeze-dried in a vacuum to obtain the mixture. The amount of the organic solvent is 200 parts; the organic solvent is dimethyl sulfoxide; the amount of the phosphorus nitrogen polymer is 60 parts; the phosphorus nitrogen polymer is poly(ethylene-chlorotrifluoroethylene); and the amount of ethylenediamine is 10 parts.
[0083] The method for preparing the flame retardant composite comprises the following steps:
[0084] (1) The modified nano core-shell flame retardant, magnesium hydroxide and surfactant were stirred and mixed, and heated at 80° C. for 240 min;
[0085] (2) The mixture obtained in step (1) is homogeneously mixed with glass fiber and montmorillonite powder, and then dried and packaged.
[0086] Implementation Method 2
[0087] The flame retardant composite has the following mass percentage composition:
[0088]
[0089] The balance is montmorillonite powder.
[0090] As for the raw materials, the diameter of the glass fiber is 10um and the length is 2mm.
[0091] The surfactant is polyoxyethylene lauryl ether.
[0092] The preparation steps of the modified nano core-shell flame retardant are as follows:
[0093] In parts by weight, 65 parts of carbon nanotubes are added to an organic solvent containing a phosphorus nitrogen polymer and ethylenediamine, and the temperature is controlled at 70°C in an oil bath while stirring. Then, under nitrogen protection, 5 parts of initiator dibenzoyl peroxide are added, and ultrasonic water bath heating is used for 6 hours. After the reaction is completed, the mixture is washed with deionized water for 5 times and vacuum freeze-dried. Among them, the amount of the organic solvent is 340 parts; the organic solvent is dimethyl sulfoxide; the amount of the phosphorus nitrogen polymer is 30 parts; the phosphorus nitrogen polymer is poly(ethylene-chlorotrifluoroethylene); and the amount of ethylenediamine is 15 parts.
[0094] The method for preparing the flame retardant composite comprises the following steps:
[0095] (1) The modified nano core-shell flame retardant, magnesium hydroxide and surfactant were stirred and mixed, and heated at 90° C. for 180 min;
[0096] (2) The mixture obtained in step (1) is homogeneously mixed with glass fiber and montmorillonite powder, and then dried and packaged.
[0097] Implementation 3
[0098] The flame retardant composite has the following mass percentage composition:
[0099]
[0100] The balance is montmorillonite powder.
[0101] As for the raw materials, the diameter of the glass fiber is 6um and the length is 4mm.
[0102] The surfactant is polyoxyethylene lauryl ether.
[0103] The preparation steps of the modified nano core-shell flame retardant are as follows:
[0104] In parts by weight, 45 parts of carbon nanotubes are added to an organic solvent containing a phosphorus nitrogen polymer and ethylenediamine, and the temperature is controlled at 78°C in an oil bath while stirring. Then, under nitrogen protection, 3 parts of initiator dibenzoyl peroxide are added, and ultrasonic water bath heating is used for 10 hours. After the reaction is completed, the mixture is washed with deionized water for 5 times and vacuum freeze-dried. The amount of the organic solvent is 240 parts; the organic solvent is dimethyl sulfoxide; the amount of the phosphorus nitrogen polymer is 50 parts; the phosphorus nitrogen polymer is poly(ethylene-chlorotrifluoroethylene); and the amount of ethylenediamine is 12 parts.
[0105] The method for preparing the flame retardant composite comprises the following steps:
[0106] (1) The modified nano core-shell flame retardant, magnesium hydroxide and surfactant were stirred and mixed, and heated at 82° C. for 230 min;
[0107] (2) The mixture obtained in step (1) is homogeneously mixed with glass fiber and montmorillonite powder, and then dried and packaged.
[0108] Implementation 4
[0109] The flame retardant composite has the following mass percentage composition:
[0110]
[0111] The balance is montmorillonite powder.
[0112] As for the raw materials, the diameter of the glass fiber is 10um and the length is 2mm.
[0113] The surfactant is polyoxyethylene lauryl ether.
[0114] The preparation steps of the modified nano core-shell flame retardant are as follows:
[0115] In parts by weight, 60 parts of carbon nanotubes are added to an organic solvent containing a phosphorus nitrogen polymer and ethylenediamine, and the temperature is controlled at 73°C in an oil bath while stirring, and then 5 parts of initiator dibenzoyl peroxide are added under nitrogen protection, and ultrasonic water bath heating is used for 6 hours. After the reaction is completed, the mixture is washed with deionized water for 5 times and vacuum freeze-dried. Among them, the amount of the organic solvent is 230 parts; the organic solvent is dimethyl sulfoxide; the amount of the phosphorus nitrogen polymer is 40 parts; the phosphorus nitrogen polymer is poly(ethylene-chlorotrifluoroethylene); and the amount of ethylenediamine is 15 parts.
[0116] The method for preparing the flame retardant composite comprises the following steps:
[0117] (1) The modified nano core-shell flame retardant, magnesium hydroxide and surfactant were stirred and mixed, and heated at 88° C. for 200 min;
[0118] (2) The mixture obtained in step (1) is homogeneously mixed with glass fiber and montmorillonite powder, and then dried and packaged.
[0119] Implementation method 5
[0120] The flame retardant composite has the following mass percentage composition:
[0121]
[0122] The balance is montmorillonite powder.
[0123] As for the raw materials, the diameter of the glass fiber is 10um and the length is 2mm.
[0124] The surfactant is polyoxyethylene lauryl ether.
[0125] The preparation steps of the modified nano core-shell flame retardant are as follows:
[0126] In parts by weight, 55 parts of carbon nanotubes are added to an organic solvent containing a phosphorus nitrogen polymer and ethylenediamine, and the temperature is controlled at 75°C in an oil bath while stirring, and then 4 parts of initiator dibenzoyl peroxide are added under nitrogen protection, and ultrasonic water bath heating is used for 8 hours. After the reaction is completed, the mixture is washed with deionized water for 5 times and vacuum freeze-dried. Among them, the amount of the organic solvent is 260 parts; the organic solvent is dimethyl sulfoxide; the amount of the phosphorus nitrogen polymer is 45 parts; the phosphorus nitrogen polymer is poly(ethylene-chlorotrifluoroethylene); and the amount of ethylenediamine is 13 parts.
[0127] The method for preparing the flame retardant composite comprises the following steps:
[0128] (1) The modified nano core-shell flame retardant, magnesium hydroxide and surfactant were stirred and mixed, and heated at 85° C. for 210 min;
[0129] (2) The mixture obtained in step (1) is homogeneously mixed with glass fiber and montmorillonite powder, and then dried and packaged.
[0130] Implementation 6
[0131] The flame retardant composite has the following mass percentage composition:
[0132]
[0133]
[0134] The balance is montmorillonite powder.
[0135] As for the raw materials, the diameter of the glass fiber is 8um and the length is 4mm.
[0136] The surfactant is polyoxyethylene lauryl ether.
[0137] The preparation steps of the modified nano core-shell flame retardant are as follows:
[0138] In parts by weight, 45 parts of carbon nanotubes are added to an organic solvent containing a phosphorus nitrogen polymer and ethylenediamine, and the temperature is controlled at 72°C in an oil bath while stirring, and then 5 parts of initiator dibenzoyl peroxide are added under nitrogen protection, and ultrasonic water bath heating is used for 10 hours. After the reaction is completed, the mixture is washed with deionized water for 5 times and vacuum freeze-dried. Among them, the amount of the organic solvent is 240 parts; the organic solvent is dimethyl sulfoxide; the amount of the phosphorus nitrogen polymer is 60 parts; the phosphorus nitrogen polymer is poly(ethylene-chlorotrifluoroethylene); and the amount of ethylenediamine is 13 parts.
[0139] The method for preparing the flame retardant composite comprises the following steps:
[0140] (1) The modified nano core-shell flame retardant, magnesium hydroxide and surfactant were mixed and heated at 80°C for 180 minutes;
[0141] (2) The mixture obtained in step (1) is homogeneously mixed with glass fiber and montmorillonite powder, and then dried and packaged.
[0142] Comparison method 1
[0143] The flame retardant composite has the following mass percentage composition:
[0144]
[0145] The balance is montmorillonite powder.
[0146] As for the raw materials, the diameter of the glass fiber is 10um and the length is 2mm.
[0147] The surfactant is polyoxyethylene lauryl ether.
[0148] The method for preparing the flame retardant composite comprises the following steps:
[0149] (1) magnesium hydroxide and a surfactant are stirred and mixed, and heated at 85° C. for 210 min;
[0150] (2) The mixture obtained in step (1) is homogeneously mixed with glass fiber and montmorillonite powder, and then dried and packaged.
[0151] Comparison method 2
[0152] The flame retardant composite has the following mass percentage composition:
[0153]
[0154]
[0155] The balance is montmorillonite powder.
[0156] As for the raw materials, the diameter of the glass fiber is 10um and the length is 2mm.
[0157] The surfactant is polyoxyethylene lauryl ether.
[0158] The method for preparing the flame retardant composite comprises the following steps:
[0159] (1) mixing carbon nanotubes, magnesium hydroxide and a surfactant, and heating them at 85° C. for 210 min;
[0160] (2) The mixture obtained in step (1) is homogeneously mixed with glass fiber and montmorillonite powder, and then dried and packaged.
[0161] Comparison method 3
[0162] The flame retardant composite has the following mass percentage composition:
[0163]
[0164] The balance is montmorillonite powder.
[0165] As for the raw materials, the diameter of the glass fiber is 10um and the length is 2mm.
[0166] The surfactant is polyoxyethylene lauryl ether.
[0167] The preparation steps of the modified nano core-shell flame retardant are as follows:
[0168] In parts by weight, 55 parts of carbon nanotubes are added to an organic solvent, and the mixture is stirred while being controlled at 75°C in an oil bath, and then 4 parts of initiator dibenzoyl peroxide are added under nitrogen protection, and ultrasonic water bath heating is used for 8 hours. After the reaction is completed, the mixture is washed with deionized water for 5 times and vacuum freeze-dried to obtain the mixture. The amount of the organic solvent used is 260 parts; the organic solvent is dimethyl sulfoxide.
[0169] The method for preparing the flame retardant composite comprises the following steps:
[0170] (1) The modified nano core-shell flame retardant, magnesium hydroxide and surfactant were stirred and mixed, and heated at 85° C. for 210 min;
[0171] (2) The mixture obtained in step (1) is homogeneously mixed with glass fiber and montmorillonite powder, and then dried and packaged.
[0172] Product application solutions
[0173] 5 parts of the prepared flame retardant composite and polyethylene masterbatch (average density: 0.940 g / cm 3 , average yield strength: 8.60MPa, melting point: 102-115°C) 80 parts, 3-methacryloxypropyltrimethoxysilane 3 parts, 2,6-di-tert-butyl-p-cresol 5 parts, use a homogenizer to homogenize, then put it into a twin-screw extruder for melt extrusion granulation, wherein the temperature of the first zone to the eighth zone of the twin-screw extruder is set to
[0174] Zone 1: 160°C,
[0175] Zone 2: 180°C,
[0176] Zone 3: 200℃,
[0177] Zone 4: 200°C,
[0178] Zone 5: 170°C,
[0179] Zone 6: 160°C,
[0180] Zone 7: 150°C,
[0181] Zone 8: 160°C; screw speed is set to 300 rpm. Finally, the pelletized product is injection molded (ArburgAllrounder injection molding machine, injection pressure 28MPa, injection speed 300mm / s, holding pressure 80MPa, melt temperature 230°C, cooling time 10s) to prepare standard specimens for testing (in accordance with the shape and size requirements of ISO 527-1 / -2 standard, specimen size example: total length 75mm, gauge length 25mm, width 5mm, thickness 2mm).
[0182] After testing, the performance parameters of implementation methods 1-6 and comparison methods 1-3 are as follows:
[0183] Embodiment 1: tensile strength 94MPa, bending strength 141MPa, heat deformation temperature 212°C, flame retardant UL-94V-0;
[0184] Embodiment 2: tensile strength 94MPa, bending strength 144MPa, heat deformation temperature 214°C, flame retardant UL-94V-0;
[0185] Embodiment 3: tensile strength 95MPa, bending strength 145MPa, heat deformation temperature 217°C, flame retardant UL-94V-0;
[0186] Embodiment 4: tensile strength 97MPa, bending strength 145MPa, heat deformation temperature 219°C, flame retardant UL-94V-0;
[0187] Embodiment 5: tensile strength 98MPa, bending strength 147MPa, heat deformation temperature 223°C, flame retardant UL-94V-0;
[0188] Embodiment 6: tensile strength 95MPa, bending strength 143MPa, heat deformation temperature 216°C, flame retardant UL-94V-0;
[0189] Comparison method 1: tensile strength 85MPa, bending strength 131MPa, heat deformation temperature 173℃, flame retardant UL-94V-2;
[0190] Comparison method 2: tensile strength 88MPa, bending strength 134MPa, heat deformation temperature 184℃, flame retardant UL-94V-1;
[0191] Comparison 3: Tensile strength 92MPa, flexural strength 138MPa, heat deformation temperature 208℃, flame retardant UL-94V-0.
[0192] In summary, the modified nano core-shell flame retardant is removed from the flame retardant composite formula of comparative method 1, and the mass percentage composition is as follows: 8% glass fiber, 35% magnesium hydroxide, 1.5% surfactant, and the balance is montmorillonite powder. The modified nano core-shell flame retardant plays a vital role in flame retardant composite materials, and its removal has a significant effect on the flame retardant properties and mechanical properties of the composite materials. This paper will analyze in detail the mechanism and performance changes of the flame retardant composite after removing the modified nano core-shell flame retardant.
[0193] Modified nano core-shell flame retardants play a role in flame-retardant composite materials mainly through the following mechanisms:
[0194] Thermal stability: The nano core-shell structure decomposes and absorbs a large amount of heat at high temperatures, reducing the temperature of the polymer surface, thereby effectively inhibiting the generation of combustible gases and preventing the spread of combustion.
[0195] Carbonization: The modified nano core-shell flame retardant decomposes at high temperature to generate a carbon layer, which can isolate oxygen and heat, further improving the flame retardant properties of the material.
[0196] Synergistic flame retardant effect: The modified nano core-shell flame retardant works synergistically with other flame retardant components (such as magnesium hydroxide and glass fiber) to form a multi-level flame retardant mechanism, significantly improving the overall flame retardant effect.
[0197] Uniform distribution: Nanotechnology makes the flame retardant more evenly distributed in the polymer matrix, enhancing the overall flame retardant properties of the material.
[0198] Flame retardant mechanism of comparison method 1
[0199] In comparison method 1, the modified nano core-shell flame retardant is removed, and the composite material mainly relies on the flame retardant properties of magnesium hydroxide, glass fiber and montmorillonite powder. The specific mechanism is as follows:
[0200] Magnesium hydroxide: Magnesium hydroxide decomposes into water and magnesium oxide at high temperatures, absorbing a large amount of heat, reducing the surface temperature of the polymer, forming a heat-insulating layer, and further enhancing the flame retardant effect. However, it is difficult for a single magnesium hydroxide to form a dense carbon layer, and the flame retardant effect is limited.
[0201] Glass fiber: Glass fiber mainly plays the role of enhancing mechanical strength and heat resistance in composite materials, but its own flame retardant effect is limited.
[0202] Montmorillonite powder: Montmorillonite decomposes at high temperatures to form a protective layer rich in oxygen atoms, which blocks the heat and mass transfer between the polymer surface and the external environment, thereby playing a certain flame retardant role, but the effect is not as significant as that of modified nano core-shell flame retardants.
[0203] Performance comparison
[0204] According to the test results, the performance parameters of comparison method 1 are as follows:
[0205] Tensile strength: 85MPa
[0206] Bending strength: 131MPa
[0207] Heat deformation temperature: 173℃
[0208] Flame retardant grade: UL-94V-2
[0209] Compared with the composite material containing the modified nano core-shell flame retardant (such as embodiments 1-6), the flame retardant performance of the comparative embodiment 1 is significantly reduced, mainly manifested as follows:
[0210] Tensile strength and flexural strength decreased: After removing the modified nano core-shell flame retardant, the mechanical properties of the composite material decreased. This is because the modified nano core-shell flame retardant not only provides flame retardant effect, but also enhances the mechanical properties of the material through its nanostructure.
[0211] Lower heat deformation temperature: The removal of the modified nano core-shell flame retardant reduces the stability of the material at high temperatures. After the removal of the dense carbon layer and thermal insulation layer formed by the nano core-shell structure at high temperatures, the material is more likely to deform at high temperatures.
[0212] Flame retardant rating decreased: from UL-94V-0 to UL-94V-2, indicating that the flame retardant performance of the material has decreased significantly. The removal of the modified nano core-shell flame retardant makes it impossible for the material to form an effective carbon layer and heat insulation layer during the combustion process, and the flame retardant effect is greatly reduced.
[0213] After removing the modified nano core-shell flame retardant, the flame retardant and mechanical properties of the composite material decreased. The modified nano core-shell flame retardant plays a key flame retardant role in the composite material, and its uniform distribution and synergistic effect significantly improve the flame retardant and thermal stability of the material. Specifically, the modified nano core-shell flame retardant effectively blocks the transfer of heat and oxygen by forming a dense carbon layer and a heat-insulating layer, thereby significantly improving the flame retardant properties of the material. In addition, the uniform distribution of the nanostructure also enhances the mechanical properties of the material. Therefore, the flame retardant effect of comparison method 1 is not as good as that of the composite material containing the modified nano core-shell flame retardant, and the removal of the modified nano core-shell flame retardant leads to a decrease in the overall performance of the material. This analysis shows that the use of modified nano core-shell flame retardants in flame-retardant composite materials is an effective means to improve the flame retardant and mechanical properties of materials, and its removal will have a significant adverse effect on the performance of the material.
[0214] At the same time, in comparison method 2, the modified nano core-shell flame retardant is replaced by carbon nanotubes. In comparison method 2, the modified nano core-shell flame retardant is replaced by carbon nanotubes. This change has a significant impact on the performance of the flame-retardant composite material. As a new type of nanomaterial, carbon nanotubes (CNTs) have received extensive attention in the field of materials science in recent years due to their excellent mechanical properties, electrical conductivity and thermal stability. This article will analyze in detail the mechanism and performance changes of the flame-retardant composite material after carbon nanotubes replace modified nano core-shell flame retardants.
[0215] Carbon nanotubes have the following remarkable properties:
[0216] High mechanical strength: Carbon nanotubes have extremely high Young's modulus and tensile strength, which can significantly enhance the mechanical properties of composite materials.
[0217] Excellent thermal and electrical conductivity: Carbon nanotubes have excellent thermal conductivity and electrical conductivity, which helps to improve the thermal stability of the material.
[0218] High surface area and nano effect: The high surface area of carbon nanotubes enables them to form a uniformly distributed network structure in composite materials, enhancing the overall performance of the material.
[0219] In flame retardant composites, the main mechanisms of action of carbon nanotubes include:
[0220] Physical barrier effect: The network structure formed by carbon nanotubes in the polymer matrix can effectively prevent the transfer of heat and oxygen, thereby improving the flame retardant properties of the material.
[0221] Carbon layer formation: During the combustion process, carbon nanotubes can promote the formation of a carbon layer, which can isolate heat and oxygen and further improve the flame retardant effect.
[0222] Synergistic effect: Carbon nanotubes work synergistically with other flame retardants (such as magnesium hydroxide, glass fiber, etc.) to form a multi-level flame retardant mechanism, significantly improving the overall flame retardant effect.
[0223] Flame retardant mechanism of comparison method 2
[0224] In comparative method 2, the mass percentage composition of the flame retardant composite material is as follows: 50% carbon nanotubes, 8% glass fiber, 35% magnesium hydroxide, 1.5% surfactant, and the balance is montmorillonite powder. The specific flame retardant mechanism is as follows:
[0225] Physical barrier effect of carbon nanotubes: The network structure formed by carbon nanotubes in composite materials can effectively prevent the transfer of heat and oxygen, thereby improving the flame retardant properties of the material.
[0226] Synergistic effect of magnesium hydroxide: Magnesium hydroxide decomposes into water and magnesium oxide at high temperature, which absorbs a large amount of heat, reduces the surface temperature of the polymer, forms a heat insulation layer, and further enhances the flame retardant effect.
[0227] Reinforcement of glass fiber: Glass fiber improves the mechanical strength and heat resistance of composite materials. Although its flame retardant effect is limited, it can further improve the overall performance of the material through synergistic effects.
[0228] Flame retardant effect of montmorillonite powder: Montmorillonite decomposes at high temperatures to form a protective layer rich in oxygen atoms, which cuts off the heat and mass transfer between the polymer surface and the external environment, thus playing a certain flame retardant role.
[0229] Performance comparison
[0230] According to the test results, the performance parameters of comparison method 2 are as follows:
[0231] Tensile strength: 88MPa
[0232] Bending strength: 134MPa
[0233] Heat deformation temperature: 184℃
[0234] Flame retardant grade: UL-94V-1
[0235] Compared with the composite material containing the modified nano core-shell flame retardant (such as embodiments 1-6), the flame retardant performance and mechanical properties of the comparative embodiment 2 are improved, but still slightly lower than the effect of the modified nano core-shell flame retardant. The main performances are:
[0236] Improved tensile and flexural strength: The high mechanical strength of carbon nanotubes significantly enhances the mechanical properties of the composite material.
[0237] Improved heat deformation temperature: The high thermal conductivity and thermal stability of carbon nanotubes improve the stability of the material at high temperatures.
[0238] The flame retardant grade has dropped slightly: from UL-94V-0 to UL-94V-1, which means that the flame retardant performance of the material has decreased, but still remains at a high level.
[0239] After replacing the modified nano core-shell flame retardant with carbon nanotubes, the flame retardant and mechanical properties of the composites were improved. Carbon nanotubes significantly improved the flame retardant properties of the materials through physical barrier effects and carbon layer formation mechanisms in composite materials. In addition, the high mechanical strength and thermal stability of carbon nanotubes also enhanced the overall performance of the material. However, the performance of carbon nanotubes in certain hybrid systems still needs to be further optimized to achieve higher flame retardant effects and mechanical properties.
[0240] In general, as a new type of nanomaterial, carbon nanotubes have broad application prospects in flame-retardant composite materials. Through reasonable material selection and precise process control, composite materials with excellent flame retardant and mechanical properties can be prepared, providing reliable solutions for cable sheath materials and other fields.
[0241] Comparative Method 3 removes poly(ethylene-chlorotrifluoroethylene) and ethylenediamine from the modified nano core-shell flame retardant. In Comparative Method 3, the modified nano core-shell flame retardant was removed, and the performance of poly(ethylene-chlorotrifluoroethylene) and ethylenediamine in the flame-retardant composite material was investigated. The modified nano core-shell flame retardant is usually evenly distributed in the polymer matrix through nanotechnology to form a dense protective layer, thereby significantly improving the flame retardant properties of the material. However, after removing this key component, the flame retardant and mechanical properties of the material will be significantly affected. This article will analyze in detail the mechanism of the flame-retardant composite material after removing the modified nano core-shell flame retardant and its performance changes.
[0242] Effect of modified nano core-shell flame retardant
[0243] Modified nano core-shell flame retardants play a role in flame-retardant composite materials mainly through the following mechanisms:
[0244] Thermal stability: The nano core-shell structure decomposes and absorbs a large amount of heat at high temperatures, reducing the temperature of the polymer surface, thereby effectively inhibiting the generation of combustible gases and preventing the spread of combustion.
[0245] Carbonization: The modified nano core-shell flame retardant decomposes at high temperature to generate a carbon layer, which can isolate oxygen and heat, further improving the flame retardant properties of the material.
[0246] Synergistic flame retardant effect: The modified nano core-shell flame retardant works synergistically with other flame retardant components (such as magnesium hydroxide and glass fiber) to form a multi-level flame retardant mechanism, significantly improving the overall flame retardant effect.
[0247] Uniform distribution: Nanotechnology makes the flame retardant more evenly distributed in the polymer matrix, enhancing the overall flame retardant properties of the material.
[0248] Flame retardant mechanism of comparison method 3
[0249] In comparative method 3, the mass percentage composition of the flame retardant composite material is as follows: 50% modified nano core-shell flame retardant, 8% glass fiber, 35% magnesium hydroxide, 1.5% surfactant, and the balance is montmorillonite powder. The specific flame retardant mechanism is as follows:
[0250] Function of poly(ethylene-chlorotrifluoroethylene): Poly(ethylene-chlorotrifluoroethylene) is a fluorinated polymer with excellent heat resistance and chemical stability. At high temperatures, the polymer can decompose to generate fluorinated compounds, which can form a protective layer on the polymer surface to isolate heat and oxygen, thereby improving the flame retardant properties of the material.
[0251] Function of ethylenediamine: As a cross-linking agent, ethylenediamine can enhance the mechanical properties and thermal stability of the material. At high temperatures, ethylenediamine can undergo cross-linking reactions with the polymer matrix to form a stable three-dimensional network structure, thereby improving the flame retardant properties of the material.
[0252] Synergistic effect of magnesium hydroxide: Magnesium hydroxide decomposes into water and magnesium oxide at high temperature, which absorbs a large amount of heat, reduces the surface temperature of the polymer, forms a heat insulation layer, and further enhances the flame retardant effect.
[0253] Reinforcement of glass fiber: Glass fiber improves the mechanical strength and heat resistance of composite materials. Although its flame retardant effect is limited, it can further improve the overall performance of the material through synergistic effects.
[0254] Flame retardant effect of montmorillonite powder: Montmorillonite decomposes at high temperatures to form a protective layer rich in oxygen atoms, which cuts off the heat and mass transfer between the polymer surface and the external environment, thus playing a certain flame retardant role.
[0255] According to the test results, the performance parameters of comparison method 3 are as follows:
[0256] Tensile strength: 92MPa
[0257] Bending strength: 138MPa
[0258] Heat deformation temperature: 208℃
[0259] Flame retardant grade: UL-94V-0
[0260] Compared with the composite material containing the modified nano core-shell flame retardant (such as embodiments 1-6), the flame retardant performance and mechanical properties of the comparative embodiment 3 are reduced, but still maintained at a high level. The main performances are:
[0261] Tensile strength and flexural strength decreased: After removing the modified nano core-shell flame retardant, the mechanical properties of the composite material decreased. This is because the modified nano core-shell flame retardant not only provides flame retardant effect, but also enhances the mechanical properties of the material through its nanostructure.
[0262] The heat deformation temperature is reduced: the removal of the modified nano core-shell flame retardant reduces the stability of the material at high temperatures. After the dense carbon layer and thermal insulation layer formed by the nano core-shell structure at high temperatures are removed, the material is more likely to deform at high temperatures.
[0263] The flame retardant grade has dropped slightly: from UL-94V-0 to UL-94V-0, which means that the flame retardant performance of the material has decreased, but it still remains at a high level.
[0264] After removing the modified nano core-shell flame retardant, the flame retardant and mechanical properties of the composite material decreased. The modified nano core-shell flame retardant plays a key flame retardant role in the composite material, and its uniform distribution and synergistic effect significantly improve the flame retardant and thermal stability of the material. Specifically, the modified nano core-shell flame retardant effectively blocks the transfer of heat and oxygen by forming a dense carbon layer and a heat-insulating layer, thereby significantly improving the flame retardant properties of the material. In addition, the uniform distribution of the nanostructure also enhances the mechanical properties of the material. Therefore, the flame retardant effect of comparison method 3 is not as good as that of the composite material containing the modified nano core-shell flame retardant, and the removal of the modified nano core-shell flame retardant leads to a decrease in the overall performance of the material. This analysis shows that the use of modified nano core-shell flame retardants in flame-retardant composite materials is an effective means to improve the flame retardant and mechanical properties of materials, and its removal will have a significant adverse effect on the performance of the material.
[0265] In addition, taking embodiment 5 as an example, the core component modified nano core-shell flame retardant involved is Figure 1 , Figure 2 As shown, the structure is uniform and dispersed uniformly, and it also has a pore structure. The modified nano core-shell flame retardant is a composite material composed of carbon nanotubes, phosphorus nitrogen polymer and ethylenediamine. Its reaction mechanism involves the interaction between these components, and the specific analysis is as follows:
[0266] The role of carbon nanotubes
[0267] Carbon nanotubes have excellent mechanical and electrical properties, and can improve the thermal stability and flame retardancy of materials. In modified nano core-shell flame retardants, carbon nanotubes can react with phosphorus nitrogen polymers and ethylenediamine to form a stable core-shell structure.
[0268] The role of phosphorus-nitrogen polymers
[0269] Phosphorus nitrogen polymer is a common flame retardant with good carbonization and gas phase flame retardant effect. In the modified nano core-shell flame retardant, phosphorus nitrogen polymer can react with carbon nanotubes and ethylenediamine to form a stable core-shell structure.
[0270] The role of ethylenediamine
[0271] As a crosslinking agent, ethylenediamine can enhance the mechanical properties and thermal stability of the material. In the modified nano core-shell flame retardant, ethylenediamine can react with carbon nanotubes and phosphorus nitrogen polymers to form a stable core-shell structure.
[0272] Reaction mechanism
[0273] The reaction mechanism of the modified nano core-shell flame retardant can be described as follows:
[0274] Carbon nanotubes, phosphorus nitrogen polymers and ethylenediamine react to form a stable core-shell structure.
[0275] The phosphorus-nitrogen polymer in the core-shell structure can undergo a carbonization reaction to form a stable carbon layer.
[0276] The char layer can prevent the spread of flames and reduce the burning rate of the material.
[0277] Ethylenediamine in the core-shell structure can enhance the mechanical properties and thermal stability of the material.
[0278] In conclusion, the reaction mechanism of the modified nano core-shell flame retardant involves the interaction between carbon nanotubes, phosphorus nitrogen polymer and ethylenediamine to form a stable core-shell structure with excellent flame retardant properties and thermal stability.
[0279] The applicant declares that the present invention is explained by the above embodiments, but the present invention is not limited to the above, that is, it does not mean that the present invention must rely on the above to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A flame retardant composite, characterized in that: The flame retardant composite has the following mass percentage composition:
2. The flame retardant composite according to claim 1, characterized in that: The flame retardant composite has the following mass percentage composition:
3. The flame retardant composite according to claim 1, characterized in that: The flame retardant composite has the following mass percentage composition:
4. The flame retardant composite according to claim 1, characterized in that: The diameter of the glass fiber is 5-10um and the length is 2-5mm.
5. The flame retardant composite according to claim 1, characterized in that: The surfactant is polyoxyethylene lauryl ether.
6. The flame retardant composite according to claim 1, characterized in that: The preparation steps of the modified nano core-shell flame retardant are as follows: In parts by weight, 40-65 parts of carbon nanotubes are added to an organic solvent containing a phosphorus nitrogen polymer and ethylenediamine, and the temperature is controlled at 70°C-80°C in an oil bath while stirring. Then, under nitrogen protection, 3-5 parts of initiator dibenzoyl peroxide are added, and ultrasonic water bath heating is used for 6h-10h. After the reaction is completed, the product is washed with deionized water for 5 times and vacuum freeze-dried.
7. The flame retardant composite according to claim 5, characterized in that: The amount of the organic solvent is 200-340 parts; The organic solvent is dimethyl sulfoxide; The phosphorus-nitrogen polymer is used in an amount of 30 to 60 parts; The phosphorus-nitrogen polymer is poly(ethylene-chlorotrifluoroethylene); The usage of the ethylenediamine is 10 parts to 15 parts.
8. A method for preparing a flame retardant composite as claimed in claim 1, characterized in that: The following steps are involved: (1) mixing the modified nano core-shell flame retardant, magnesium hydroxide and a surfactant, and heating the mixture at 80° C. to 90° C. for 180 min to 240 min; (2) The mixture obtained in step (1) is homogeneously mixed with glass fiber and montmorillonite powder, and then dried and packaged.
Citation Information
Patent Citations
Montmorillonite composite fire retardant
CN103232851A
Efficient composite flame retardant
CN103588994A
Phosphorus-nitrogen nano flame retardant of core-shell structure and preparation method thereof
CN105237810A
